PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN MEDIA GAMBAR SERI PADA SISWA SDN 15 BENTARAT - Purwanti,, Ika Siti; Halidjah, Siti; Margiati, K.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to improve the ability on writing a description using picture series towards the third grade students of SD Negeri 15 Bentarat Kabupaten Bengkayang. The method used is descriptive. The form of this research is classroom action research with participation collaborative as its charachteristics. The subject of this research 26 students of the third grade. This research is done in three cycle: planning, implementing, observing, and reflecting. Technique of the data collection is direct observation and measurement with the observation sheets and formative test as the tool of collecting the data. Technique of the data analysis used is calculating the mean score. The result of this research is (1)the ability on teacher’s planning in writing description using picture series is 3,45 in the first cycle, 3,75 cycle in the second cycle, and 3,75 in the third cycle; (2) the ability on teacher’s implementation in writing description using picture series is 2,55 in the first cycle, 3,26 cycle in the second cycle, and 3,75 in the third cycle; (3) the result of students’ score is 62,80 in the first cycle, 79,50 in the second cycle, and 82,92 in the third cycle. By those data, it can be concluded that using picture series in learning Bahasa Indonesia can improve students’ ability on writing a description.  Keywords: Improving, Writing, Description, Picture Series